2016
DOI: 10.1016/j.pnpbp.2015.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial direct current stimulation (tDCS) reverts behavioral alterations and brainstem BDNF level increase induced by neuropathic pain model: Long-lasting effect

Abstract: tDCS reverts behavioral alterations associated to neuropathic pain, indicating possible analgesic and anxiolytic tDCS effects. tDCS treatment induces changes in the BDNF levels in different regions of the central nervous system (CNS), and this effect can be attributed to different cellular signaling activations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 96 publications
7
21
0
Order By: Relevance
“…In our study, the anode stimulation electrode was mounted contralateral or ipsilateral to the injured paw to measure the antinociceptive effect of tDCS, and our results demonstrated that both locations of A-tDCS led to significant decreases in pain. Our study supplements previous experiments in which the location of the electrode was not taken into consideration (Cioato et al, 2016; Filho et al, 2016). A possible mechanism of these results is supra-spinal antinociceptive activities via multiple parallel pathways (Pertovaara and Wei, 2003).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In our study, the anode stimulation electrode was mounted contralateral or ipsilateral to the injured paw to measure the antinociceptive effect of tDCS, and our results demonstrated that both locations of A-tDCS led to significant decreases in pain. Our study supplements previous experiments in which the location of the electrode was not taken into consideration (Cioato et al, 2016; Filho et al, 2016). A possible mechanism of these results is supra-spinal antinociceptive activities via multiple parallel pathways (Pertovaara and Wei, 2003).…”
Section: Discussionsupporting
confidence: 89%
“…Numerous clinical studies have concluded that A-tDCS is an effective method for pain modulations, which is helpful at reducing both fibromyalgia and spinal cord injury related-pain (Fregni et al, 2006; Roizenblatt et al, 2007; Soler et al, 2010). There are also studies showing effects of A-tDCS in inflammatory and neuropathic pain in animals (Laste et al, 2012; Spezia Adachi et al, 2012; Cioato et al, 2016; Filho et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…The positive effects produced by the modulation of the glutamatergic system could eventually lead to the release of the brain-derived neurotrophic factor (BDNF) [ 55 ]. In fact, tDCS has shown to change the BDNF [ 56 ] promoting the BDNF-dependent synaptic plasticity [ 22 ].…”
Section: Understanding and Differentiating Tdcsmentioning
confidence: 99%
“…All possible measures were taken to minimize animal suffering and external sources of pain and discomfort. In addition, the minimum number of animals required to produce reliable scientific data was used based on previous studies of our research group that used similar methods (Spezia Adachi et al, ; Laste et al, ; Spezia Adachi et al, ; Schunck et al, ; Macedo et al, ; Filho et al, , Cioato et al, ).…”
Section: Methodsmentioning
confidence: 99%